Insulinoma camouflaged by vague neuroglycopenic symptoms: A case report (Indian Journal of Case Reports, 2020)
Pancreatic endocrine tumors are rare lesions, with a reported incidence of four cases per 1 million patients per year. Of them, insulinomas are the most common. These are usually benign, solitary, and small size (<2 cm in diameter). Most are sporadic; however, 10% are multiple and occur as part of multiple endocrine neoplasia syndrome type I. Chronic hypoglycemia due to an insulinoma often presents with neuroglycopenic symptoms that can easily be mistaken for neurological or psychiatric symptoms, especially in developing countries. This may result in delayed diagnosis with associated complications. We hereby present the case of a 45-year-old female from the rural background that initially sought treatment by a psychiatrist for her vague neurological symptoms and were later diagnosed to have insulinoma.